AED Withdrawal: Risk Factors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
The results of a prospective cohort study to investigate the effects of withdrawal of AEDs in 264 children with epilepsy after a mean seizure-free interval of 2.9 years are reported from the Montefiore/Einstein Epilepsy Management Center, Bronx, NY.